Restoring Tissue Homeostasis at Metastatic Sites: A Focus on Extracellular Vesicles in Bone Metastasis - Giannandrea, Domenica; Citro, Valentina; Lesma, Elena; Bignotto, Monica; Platonova, Natalia; Chiaramonte, Raffaella (Frontiers in Oncology, 2021)
Bone is the most common site of cancer metastasis and the spread of cancer cells to the bone is associated with poor prognosis, pain, increased risk of fractures and hypercalcemia. Bone marrow microenvironment is an attractive place for tumor dissemination, due to the dynamic network of non-malignant cells. In particular, the alteration of the bone homeostasis favors the tumor homing and the consequent osteolytic or osteoblastic lesions. Extracellular vesicles (EVs) are reported to be involved in metastatic process promoting tumor invasion, escape from immune surveillance, extravasation, extracellular matrix remodeling and metastasis. On the other hand, the role of EVs in bone metastases is still an open field. Current results suggest the ability of tumor derived EVs to promote bone localization and metastasis formation, altering the physiological balance between bone destruction and new bone depositions. Moreover, EVs from the bone marrow niche may support tumor metastasis onset. In this review, we summarize the most recent findings concerning the role played by EVs in the pathological alterations of homeostasis occurring during bone metastasis. The final purpose is to show up novel potential EV-based therapeutic options to inhibit metastasis formation.